Time course and metabolic costs of a humoral immune response in the little ringed plover charadrius dubius - Abad Gómez-Pantoja, José María; Sánchez Gutiérrez, Jorge; Villegas Sánchez, María Auxiliadora; Sánchez Guzmán, Juan Manuel; Masero Osorio, José Antonio (Physiological and Biochemical Zoology, 2013)
Despite host defense against parasites and pathogens being considered a costly life-history trait, relatively few studies have assessed the energetic cost of immune responsiveness. Knowledge of such energetic costs may help to understand the mechanisms by which trade-offs with other demanding activities occur. The time course and associated metabolic costs of mounting a primary and secondary humoral immune response was examined in little ringed plovers Charadrius dubius challenged with sheep red blood cells. As was expected, the injection with this antigen increased the production of specific antibodies significantly, with peaks 6 d postinjection in both primary and secondary responses. At the peak of secondary antibody response, the antibody production was 29% higher than that observed during the primary response, but the difference was nonsignificant. Mounting the primary response did not significantly increase the resting metabolic rate (RMR) of birds, whereas the secondary response did by 21%, suggesting that the latter was more costly in terms of RMR. In spite of the fact that the primary response did not involve an increase in RMR, birds significantly decreased their body mass. This could imply an internal energy reallocation strategy to cope with the induced immune challenge. Last, we found that RMR and antibody production peaks were not coupled, which could help to conciliate the variable results of previous studies. Collectively, the results of this study support the hypothesis that humoral immunity, especially the secondary response, entails energetic costs that may trade-off with other physiological activities. Financial support was provided by projects CGL2011- 27485 (Ministerio de Economı´a y Competitividad and European Regional Development Funds [ERDF]) and GR10174 (Gobierno de Extremadura and ERDF) peerReviewed